PENERAPAN MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT DALAM MENINGKATKAN HASIL BELAJAR DI SMPN 1 LAMBU - Rahman, Aly Fathur; Bunyamin, Andi; Syahrul, Muhammad; Mustamin; Raehana, Syarifa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to improve students’ learning outcomes through the implementation of the Teams Games Tournament (TGT) cooperative learning model in Islamic Religious Education for class VIII.C at SMPN 1 Lambu, Bima Regency. This research employed Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The research subjects were 23 students. Data were collected through observation and learning outcome tests, and analyzed using descriptive quantitative and qualitative methods. The findings indicated that the implementation of the TGT model significantly improved students’ learning activities and outcomes. In Cycle I, learning mastery had not yet reached the predetermined success indicators; therefore, improvements were made in Cycle II. In Cycle II, learning mastery increased to 86.96% with an average score of 87.08, categorized as very high. Students’ participation, discipline, enthusiasm, and understanding of the material also showed significant improvement. In conclusion, the Teams Games Tournament (TGT) cooperative learning model is effective in improving students’ learning outcomes in Islamic Religious Education.